2021
DOI: 10.3389/fchem.2021.683765
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Degradation of Methylene Blue by WO3 Nanoparticles Under NIR Light Irradiation

Abstract: Photocatalysts have been paid great attention owing to their excellent performance in the degradation of dangerous organic pollutants. Herein, a novel longitudinally grown WO3 photocatalyst was prepared by using a hydrothermal process, which had strong ultraviolet, visible light absorption, and weak near-infrared (NIR) absorption. The WO3 photocatalyst exhibited excellent performance in the rapid degradation of methylene blue (MB) in industry. The photothermal effect is mainly responsible for the rapid degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Photodegradation of MB also observed by decrease in maximum absorption peak intensity (λ max = 664 nm) in UV‐visible spectrum (figure 6b). [ 13 ] The presence of RGO in RGO@MIL‐53(Fe) hybrid not only catalyse the degradation of MB and RhB but can also adsorb the MB and RhB molecules. This phenomenon demonstrates that presence of RGO not only provide high surface area for dye adsorption but also lower the recombination rate of e ‐ and h + in photo excited MIL‐53(Fe) to enhance the photodegradation activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodegradation of MB also observed by decrease in maximum absorption peak intensity (λ max = 664 nm) in UV‐visible spectrum (figure 6b). [ 13 ] The presence of RGO in RGO@MIL‐53(Fe) hybrid not only catalyse the degradation of MB and RhB but can also adsorb the MB and RhB molecules. This phenomenon demonstrates that presence of RGO not only provide high surface area for dye adsorption but also lower the recombination rate of e ‐ and h + in photo excited MIL‐53(Fe) to enhance the photodegradation activity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their promising qualities, they represent an effective contender for a variety of applications including medicines, administration, energy conversion, light harvesting, gas storage, and environmental clean-up. [11][12][13] MOFs can be photoexcited suitably when interacting with incident light that matches their energy in respect of ligand-to-metal charge-transmission. [14] Garcia and colleagues in their study have described a typical MOF-5 as an effective photo-catalyst for the breakdown of phenol.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the observed enhancement of methylene blue (MB) adsorption occurs through the p-p aromatic stacking interactions between the aromatic ring of MB molecules and the ZnBTSC2@GO hybrid, resulting in non-covalent adsorption, in line with other studies that reported similar features when ZnO or WO 3 were used in MB degradation studies. 77,78 Recent studies highlight the unique physical and photoelectric properties of transition metal functionalised bis(thiosemicarbazones), which positioned them as novel and efficient photocatalysts for organic dyes under similar conditions. 79 A possible reason is that the valence band of these thiol-substituted metal complexes exhibits a more negative energy level relative to the O 2p orbitals, enabling smaller band gaps and therefore increased susceptibility to visible light.…”
Section: And Esi †)mentioning
confidence: 99%
“…Basically, a catalyst solution that is irradiated by light produces pairs of electrons (e) and holes (h+). The photocatalytic activity increases due to retained a large number of these photo-excited holes and the proportion of active surfaces [19], [20].…”
Section: Degradation Of Methylene Blue By Cao-mnfe2o4 Nanoparticlesmentioning
confidence: 99%